Descriptive study showing the effect of small differences in entry scores on retention and success in six courses in nursing - Sheila A. Doggrell (BMC, 2024)
Abstract Background Undergraduate enrolments and completions in nursing are declining at the same time as requirements for registered nurses in the workforce is increasing. One way to increase enrolments is to lower entry requirements into nursing programs. This study determined the effect of a small lowering of entry scores on the retention and success rates. The study was undertaken at Griffith University, where identical bioscience and clinical courses run at three campuses, one with a lower- than normal-entry score and two with the normal-entry requirements. Methods A comparison of the 62-148 students enrolled in the courses at the lower- than normal- (lesser) entry requiring campus with the 197-288 students enrolled in the courses in one normal-entry requiring campuses. For individual courses (4 bioscience and 2 clinical courses) retention rates were measured and compared between campuses/cohorts. For completing students, we measured success as (i) Academic outcomes; overall marks and marks for the exam and coursework and (ii) Failure rates in the examination and coursework. Data analysis was by Student's t-test and Odds ratio. Results For all courses, there were few significant differences in measures of retention and success between the lower- and normal-entry campuses, and all differences were small. Comparing the campuses; (a) For all courses, progression rates were similar. (b) For completing students, passing rates were similar in the bioscience courses, but higher in the normal- than lower-entry campus for the clinical courses. (c) In the bioscience courses, the overall marks were similar, but in the clinical courses, the overall mark was slightly higher in the normal- than lower-entry campus. (d) The overall failure rates were similar for the biosciences, but higher for the lower- than normal-entry cohort in the clinical courses. (e) The failure rates in exams were similar between cohorts in all courses. Conclusions This study shows that small changes in entry requirements for a nursing program had minimal effects on retention. The differences in entry requirements also did not affect the success of students in the bioscience courses. Decreasing entry requirement for nursing programs may be a way to increase nursing graduates.